Botanical, Pharmacognosy, and Phytochemical Studies of Sintrong Leaves (Crassocephalum crepidioides) Growing in Tanjung Setia Village, West Coast, Lampung: Kajian Botani, Farmakognosi, dan Fitokimia Daun Sintrong (Crassocephalum crepidioides) yang Tumbuh di Desa Tanjung Setia Pesisir Barat Lampung - Anindita, Reza; Pratama, Gita Cahya; Putri, Intan Kurnia; Beandrade, Maya Uzia; Futihat, Chilyati Eky (Department of Biology Faculty of Mathematics and Natural Sciences Universitas Lampung in collaboration with The Indonesian Association of Biology (PBI) Lampung Branch., 2025)
Crassochepalum crepidioides plant has antibacterial and anti-wound properties. This study aims to determine the botanical profile, microscopic powder, phytochemical screening, and Thin Layer Chromatography (TLC). This study aims to determine the morphology of leaves, stems, roots, microscopic powder, phytochemical screening, and Thin Layer Chromatography (TLC) of C. crepidioides leaves from Tanjung Setia Village West Coast Lampung, Indonesia. Methods include morphological examination, microscopic powder, phytochemical screening, and TLC. The results of the botanical show oval-shaped leaves, pointed tips, pinnate veins, serrated edges, smooth leaf surface, soft wood stems, and tap roots. Microscopic observation found fragments of stomata. Positive phytochemical screening of alkaloids, flavonoids, saponins, and tannins. TLC test spot with five spots (red) and an average Rf value of 0.21-0.97. Concludes that the thin layer chromatography test is thought to produce flavonoid spots at an Rf value of 0.72-0.77.